Relationships between Nursing Students’ Attitudes Toward the Nursing Profession, Fear of COVID-19, and Intolerance of Uncertainty: A Cross-sectional Study - Banu Terzi; Fatma Azizoğlu; Çağla Seven (Makara Journal of Health Research, 2023)
Background: Nursing students were caught unprepared for the COVID-19 pandemic. Both the inability to control the epidemic and the interruption of education caused students to experience fear, anxiety, and uncertainty. This study investigates the relationships between nursing students’ attitudes toward the nursing profession and their fear of COVID-19 and intolerance of uncertainty.